Dimer ion formation and intermolecular fragmentation of 1, 2‐diacylglycerols revealed by electrospray ionization Fourier transform ion cyclotron resonance mass spectrometry for more comprehensive lipid analysis. (25th June 2014) - Müller, Constanze; Kanawati, Basem; Rock, Theresa M.; Forcisi, Sara; Moritz, Franco; Schmitt‐Kopplin, Philippe
<x xml:space="preserve">Abstract</x> RATIONALE The ionization of neutral diacylglycerols (DAGs) by electrospray ionization mass spectrometry (ESI‐MS) is challenging compared with other lipid classes which possess ionic head group conjugations. Although ESI‐MS is the method of choice in lipidomic analysis, it is questionable whether all lipid classes can be efficiently ionized by this method. Actually, various lipids were not efficiently detected (due to poor ionization) in many studies which claimed to comprehensively describe lipid profiles. Since neutral lipids are precursors for the biosynthesis of most other lipid classes, the necessity for improved or alternative ionization and identification schemes becomes obvious. METHODS We identified the 1, 2‐diacylglycerol (DAG) dimer ion formation in the gas phase by ultra‐high‐resolution Fourier transform ion cyclotron resonance mass spectrometry (FT‐ICR‐MS) in negative electrospray ionization ((−)ESI) mode. The geometry of the dimer ion was investigated by accurate density functional theory (DFT) calculations at the B3LYP/6‐311+G(d)//B3LYP/LANL2DZ level of theory. Fragmentation of the dimer ions of many investigated DAGs has been achieved via collision‐induced dissociation (CID) experiments with several elevated collision energies (0–12 eV). RESULTS We revealed the possibility to ionize neutral DAGs as dimer ions in the negative ESI mode. Quantum mechanical calculations revealed a polar head‐to‐head intermolecular interaction between one charged DAG and one DAG neutral. This represents an energy minimum structure for the DAG dimer ions. We could furthermore detect CID fragmentation product ions that can only result from intermolecular reactions in this head‐to‐head conformation (SN2 nucleophilic substitution reactions inside the dimer DAG ion). CONCLUSIONS Here, we present for the first time the opportunity to ionize and identify DAGs as dimer ions. This new finding provides a new alternative for investigations of important diacylglycerol lipids and provides the opportunity to obtain complementary and more comprehensive results in future lipidomic studies. Copyright © 2014 John Wiley & Sons, Ltd.